Aksi Rehabilitasi Mangrove Sebagai Upaya Mendorong Ecoeduwisata Mangrove Di Kelurahan Parangloe, Kecamatan Tamalanrea, Kota Makassar - Rahman, Rahman; Rahmat, Rudi; Achmad, Nur Ilmi; Lokollo, Frijona F; Fakaubun, Fahrul R (PENGAMATAN: Jurnal Pengabdian Masyarakat untuk Ilmu MIPA dan Terapannya, 2025)
The degradation of mangrove forests in Parangloe Village, Makassar City, prompted the implementation of an integrated mangrove rehabilitation program through an eco-edu-tourism approach. This initiative aimed to restore coastal ecosystems while enhancing community awareness and participation through environmental education. A total of 3,000 Rhizophora sp. seedlings were planted collaboratively by over 100 local residents, reflecting strong social involvement. The outcomes demonstrated significant ecological impacts, including shoreline stabilization, habitat provision for coastal biota, and blue carbon sequestration. Socially, the program fostered community solidarity, improved environmental literacy, and created economic opportunities through the development of educational tourism. Mangrove rehabilitation based on eco-edu-tourism has proven to be an effective strategy that integrates conservation, education, and community empowerment toward sustainable coastal development.